APLIKASI KITOSAN UNTUK PENGENDALIAN PENYAKIT BUSUK BUAH KAKAO (Phytophthora megakarya L.) - Septiana Septiana; Suskandini Ratih Dirmawati; Rusdi Evizal (Universitas Lampung, 2020)
Research on the effect of chitosan concentration on the severity of cocoa pod rot in three different sizes of cocoa pods carried out at the smallholder cocoa plantations in Taman Endah Village, East Lampung Regency using local hybrid cocoa. Data analysis was using analysis of variance (ANOVA) and continued with Duncan's multiple range test at 5% level. The results showed that the severity of fruit rot at cocoa pod sprayed with copper oxide 56% and chitosan 0.6% was lower than the severity of fruit rot with application of chitosan 0.2%, 0.4%, and 0.8% and control..Keywords: application, chitosan, cocoa pod rot disease